Analyzing Conceptual Understanding of Work and Energy: Insights for Improving Physics Instruction - Sangkala, Nur Rahmah; Yusal, Yulianti; Annam, Syarful; Rahmadani, Amalia; Alfatih, Ainun Najib (Journal of Authentic Research, 2025)
This study aimed to analyse university students’ conceptual understanding of Work and Energy. A qualitative descriptive approach was applied to 36 undergraduate students enrolled in the Fundamentals of Science course at Universitas Negeri Makassar during the 2025/2026 academic year. Data were collected through a written assessment consisting of eight multiple choice and one short-answer question targeting both basic and higher-order concepts. Results show that students demonstrated strong understanding of Work concepts, particularly the relationship between force, displacement, and work. However, their grasp of Energy – especially energy transformation and conservation – was limited. The average score was 75.61%, with moderate variability and a negatively skewed distribution. These findings indicate that while procedural understanding is well developed, conceptual integration remains weak. The study recommends the use of inquiry-based and representational learning strategies to strengthen students’ conceptual reasoning in Work and Energy.